Genomic insights into the emergence and spread of antimicrobial-resistant bacterial pathogens - Baker, S; Thomson, N; Weill, F-X; Holt, KE (American Association for the Advancement of Science, 2018)
Whole-genome sequencing (WGS) has been vital for revealing the rapid temporal and spatial evolution of antimicrobial resistance (AMR) in bacterial pathogens. Some antimicrobial-resistant pathogens have outpaced us, with untreatable infections appearing in hospitals and the community. However, WGS has additionally provided us with enough knowledge to initiate countermeasures. Although we cannot stop bacterial adaptation, the predictability of many evolutionary processes in AMR bacteria offers us an opportunity to channel them using new control strategies. Furthermore, by using WGS for coordinating surveillance and to create a more fundamental understanding of the outcome of antimicrobial treatment and AMR mechanisms, we can use current and future antimicrobials more effectively and aim to extend their longevity.